A TTIP lehetséges hatásai Magyarország gazdaságára - Varga, József; Ary, Tamás (Közép-Európai Közlemények, 2016)
The editors study the Transatlantic Trade and Investment Partnership, which is being formed between the EU and the USA. The purpose of the publication is to trace the potential effects of the TTIP on the economy of Hungary.The editors show the changes of the environment of the world economy, that have established the creation of the TTIP concept. Within this, they deal with the situation that came into being because of the existence of the Eurasian Economic Union. After that, the editors shortly delineate the objective of the TTIP. Then they analyze the potential effects of the TTIP on Hungary based on the impact assessment of TTIP and the structure and economic facilities of Hungary and the European Union. Within this, first they analyze the potential macroeconomical impacts, then they make a detailed analysis on some emphasized national economical branches –out of which they find the impact on energetics, vehicle industry, agriculture and food industry primary. In these areas the editors sum up the possibilities and the risks of the TTIP. In the last part József Varga and Tamás Ary analyze the possible future of the potential effect on the European Union of the TTIP.